2019
DOI: 10.1371/journal.pone.0213000
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of standard-issue packed red blood cells induces pulmonary vasoconstriction in critically ill patients after cardiac surgery—A randomized, double-blinded, clinical trial

Abstract: BackgroundExperimental and volunteer studies have reported pulmonary vasoconstriction during transfusion of packed red blood cells (PRBCs) stored for prolonged periods. The primary aim of this study was to evaluate whether transfusion of PRBCs stored over 21 days (standard-issue, siPRBCs) increases pulmonary artery pressure (PAP) to a greater extent than transfusion of PRBCs stored for less then 14 days (fresh, fPRBCs) in critically ill patients following cardiac surgery. The key secondary aim was to assess wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
2
4
0
2
Order By: Relevance
“…They showed a significant rise in wedge pressure after transfusion; however, they lacked a fluid control group. Additionally, a recent large observational study in intensive care unit patients showed an increase in PCWP after transfusion, as well as a cardiac surgery study showing similar results . We see a similar effect of transfusion on capillary pressures; however, with our RL‐infused control group, we show that this increase is specifically transfusion product related.…”
Section: Discussionsupporting
confidence: 80%
“…They showed a significant rise in wedge pressure after transfusion; however, they lacked a fluid control group. Additionally, a recent large observational study in intensive care unit patients showed an increase in PCWP after transfusion, as well as a cardiac surgery study showing similar results . We see a similar effect of transfusion on capillary pressures; however, with our RL‐infused control group, we show that this increase is specifically transfusion product related.…”
Section: Discussionsupporting
confidence: 80%
“…Storage lesion may be an alternative pathway leading to hydrostatic pulmonary oedema after transfusion. Baron-Stefaniak et al compared fresh versus standard-issued RBCs and suggested PAP increase in the latter [14]. We transfused fresh RBCs and confirmed their finding that RBCs stored for 3 days did not alter PVRI.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies assessing the effect of allogeneic RBC transfusion on hydrostatic pressure have found a pulmonary capillary wedge pressure (PCWP) rise of 3 mmHg in chronic anaemic patients following transfusion [12,13], and suggested pulmonary artery pressure (PAP) increases after standard-issue versus fresh RBCs in critically ill patients [14]. A volunteer study showed an increase in the mean PAP following autologous transfusion of 1 unit of stored RBCs [15].…”
Section: Introductionmentioning
confidence: 99%
“…Повышение концентрации гемоглобина вслед за переливанием ЭСК хотя и может способствовать улучшению глобальной доставки кислорода, но ожидаемое повышение оксигенации тканей при этом наблюдаются лишь у малой части больных [64,65]. Объясняться это может либо причинами дисбаланса между доставкой и потреблением кислорода, не связанными с анемией, т. е. переливание ЭСК не было обусловлено клинической ситуацией, не являлось показанным и, следовательно, не было эффективно, либо изменениями донорских ЭСК, происходящих в процессе заготовки, переработки и хранения [66][67][68][69][70][71][72][73]. Большое количество клинических сравнений безопасности и эффективности, предпринятых у разных категорий больных, в том числе объединенные в метаанализы, не выявило преимуществ высоких или низких триггеров трансфузий ЭСК на основании концентрации гемоглобина.…”
Section: Notes Cpb -Cardiopulmonary Bypass Ards -Acute Respiratory Distress Syndrome or -Odds Ratio CI -Confidence Interval Rr -Relative unclassified